Níveis de energia, casca de soja e complexo enzimático na nutrição de frangos de corte - Erivelto Vilela Filho (2022)
The objective was to evaluate the use of soybean oil in low-energy diets through the inclusion of dietary fiber from soybean hulls and an enzyme complex in broilers from 20 to 36 days of age. A total of 360 Ross® male broilers were used, distributed in a completely randomized design using six isoprotein treatments with 19.5% CP: treatment A (control) 3,150 kcal/kg; treatment B with 3,120 kcal/kg of energy and use of soybean oil; treatment C with 3,120 kcal/kg of energy, including soybean hulls and use of soybean oil in the control diet; treatment D with 3,150 kcal/kg of energy and inclusion of an enzymatic complex; treatment E with 3,150 kcal/kg with the use of soybean oil from the control diet, inclusion of soybean hulls as a source of fiber and inclusion of an enzymatic complex; treatment F with 19.5% CP, 3,120 kcal/kg with the inclusion of soybean oil in the control diet, inclusion of soybean hulls as a source of fiber and inclusion of an enzymatic complex. Four replicates were used for each treatment. The quality of the pellet produced and performance variables of the birds were evaluated, such as: feed consumption, weight gain, feed conversion, viability, productive efficiency index and feed cost/kg feed. After the birds were slaughtered, at 36 days, carcass, cuts and digestive organs yields were evaluated. There was an effect of the treatments on the quality of the pellet (P<0.05), with treatment D being the one that showed the best durability of the pellets in relation to the other treatments. The results presented show that there was no effect of treatments on performance and carcass yield (P>0.05), but the production cost was lower in treatment D (P<0.05). All treatments showed excellent pellet quality results, even so there was an influence between treatments on pellet quality. There was no effect of treatments on dietary energy levels. Soybean hulls can be used as a fiber source in broiler diets without affecting the performance and carcass yield of broilers. The use of enzymes reduced the cost of chicken produced even without the inclusion of soybean hulls. More studies should be carried out in order to adjust the cost with the use of oil, fiber and enzymes.